Effect of silicone oil heat treatment on the chemical composition, cellulose crystalline structure and contact angle of Chinese parasol wood. (15th May 2017) - Okon, Kufre Edet; Lin, Fengcai; Chen, Yandan; Huang, Biao
Highlights: Changes in chemical constituents of SOHT Chinese parasol wood samples were investigated. Cellulose crystalline structure of untreated and silicone oil treated wood samples was studied. Contact angle was measured on the untreated and SOHT wood samples. Crystallinity index of cellulose increased after SOHT of the wood samples. Abstract: The effect of silicone oil heat treatment (SOTH) on the chemical composition, cellulose crystalline structure, thermal degradation and contact angle of Chinese parasol wood were examined in this study. Samples were heated at 150 °C, 180 °C and 210 °C for 2 h and 8 h, after SOHT chemical composition, fourier transformed infrared (FTIR), thermogravimetric analysis (TGA) and X-ray diffraction (XRD) of the treated samples were evaluated. Results showed that the chemical components of the wood were affected after SOHT particularly when treated at 210 °C for 8 h. Changes in the chemical components was due to the degradation of biopolymer components of the wood during SOHT. The crystallinity index of cellulose and contact angle of the SOHT samples was increased. The findings demonstrate the potential of SOHT for modification of wood. Thus an economical and eco-friendly approach to thermally modified wood was achieved in this study.